Edith Stein in the Light of the Icon - Grzegorczyk, Anna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
In this article discussed is the phenomenon of icon sui generis and a phenomenon of Edith Stein as anicon. Stein’s philosophy of Light is inscribed into a philosophical lineage of the icon, especially platonic and neoplatonic, what leads to creating an idea of iconic cognition – its foundation is a connection between trace and reflection revealed in an icon which is both a representation and a presence of God. By referring to Stein’s late philosophy as well as her biography the author describes a merge between those two domains which leads to an absolute, iconic cognition and therefore allows presenting Stein as an iconic figure, which power reveals itself in her supernatural emanation. This emanation as well as a symbiosis between cognition and existence creates an essence of Edith Stein’s phenomenon.